2019
DOI: 10.1155/2019/9191328
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Fingerprint of Erlotinib: FTIR, RS, and DFT Studies

Abstract: In this study, we provide the first Fourier-transform infrared absorption spectroscopy (FTIR) and Raman spectroscopy (RS) analysis of a vibrational fingerprint of erlotinib, a drug which is applied in non-small cell lung cancer therapy, in solid state and solution in different pH conditions. Additionally, the performed DFT theoretical calculations in vacuum and PCM models support the interpretation of vibrational spectra and give insight into an optimized spatial configuration of the investigated drug. e prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…This vibration also contributes to the bands at 1,578, 1,416, and 1,361 cm −1 . The observed AFM-IR spectral pattern for non-adsorbed erlotinib corresponds to the previously published results obtained by conventional Fourier transform IR spectroscopy in ATR mode [48]. However, some changes, especially in the relative intensities of the particular bands, are noted, especially for the bands at ~ 1,632 and ~ 1,445 cm −1 .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This vibration also contributes to the bands at 1,578, 1,416, and 1,361 cm −1 . The observed AFM-IR spectral pattern for non-adsorbed erlotinib corresponds to the previously published results obtained by conventional Fourier transform IR spectroscopy in ATR mode [48]. However, some changes, especially in the relative intensities of the particular bands, are noted, especially for the bands at ~ 1,632 and ~ 1,445 cm −1 .…”
Section: Resultssupporting
confidence: 87%
“…Figure 3(a) presents the AFM-IR spectrum of erlotinib alone, and in Table 1, all wavenumbers and assignments of the bands are listed. The band assignment analysis was performed based on previously published studies of the erlotinib structure coupled with density functional theory (DFT) calculations [48]. Additionally, the corresponding data for the main chemical groups present in the molecules such as aniline [49], pyrimidine [50,51], and phenylacetylene [52] were taken into consideration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 14 ] The structural investigations, density functional theory (DFT) studies on selpercatinib and IR spectroscopy with DFT studies of erlotinib were reported. [ 15,16 ] Due to the anti‐cancerous activity of lorlatinib (LTB), the reactivity analysis together with AIM and MD simulations are reported.…”
Section: Introductionmentioning
confidence: 99%